Factors associated with physical activity participation in adults with chronic cervical spine pain: a systematic review. Issue 1 (March 2018) - Mansfield, Michael; Thacker, Michael; Spahr, Nicolas; Smith, Toby
Abstract: Objective: To determine the factors associated with physical activity participation in adults with chronic cervical spine pain. Methods: A systematic review was conducted including searches of PubMed (MEDLINE), EMBASE and CINAHL from inception to June 12th, 2016. Grey literature and reference checking was also undertaken. Quantitative studies including factors related to physical activity participation in adults with chronic cervical spine pain were included. Two independent authors conducted the searches, extracted data and completed methodological quality assessment. Results: A total of seven studies met the selection criteria, however, four papers were finally included in the final review. A modified Downs and Black criteria was used to assess methodological quality, each study included was classed as moderate quality. A total of six factors were assessed against physical activity participation for people with chronic neck pain. These included: pain, fear of movement, smoking habits, socioeconomic status, gender, leisure and work time habits. A significant relationship was demonstrated between pain, leisure and work time habits and physical activity. Subjects were less likely to participate in physical activity if they were in pain. Subjects with neck pain were less likely to participate in physical activity in their leisure and work time. Conclusion: This review, based on a small number of heterogeneous studies demonstrated key factors that are likely to affect physical activity in people with chronic neck pain, most notably, pain levels, leisure and work habits. This review suggests that more in-depth, high quality studies are required to fully understand the impact of chronic pain on physical activity. Systematic review registration number: PROSPERO CRD42015027970.